ChemInform Abstract: Palladium‐Catalyzed Coupling of Polyfluorinated Arenes with Heteroarenes via C—F/C—H Activation. Issue 30 (4th July 2013) - Yu, Daohong; Lu, Long; Shen, Qilong
Abstract The first Pd‐catalyzed coupling of 2‐pyridyl‐polyfluoroarenes and various heteroazoles is presented.